Digital Comics Learning Media Based on Problem Based Learning in Science Subjects for Fourth Grade Elementary School - Puriasih, Kadek Nita; Trisna, Gusti Ayu Putu Sukma (Universitas Pendidikan Ganesha, 2022)
In online learning activities, the material presented by the teacher is still very limited, one of which is science learning and animal life cycle material. It makes it difficult for students to learn. This study aimed to develop PBL-based digital comics learning media in science subjects for animal life cycle material for grade IV elementary school. This type of research is developed using the ADDIE model. The research subjects consisted of two material experts and two learning media experts. The trial subjects were two practitioners by the teacher and five fourth-grade students (individual trial). The methods used in collecting data are interviews, observations, and questionnaires. The instrument used in collecting data is the rating scale instrument. The data analysis techniques are descriptive, qualitative, and quantitative. The study's results were the assessment of the material expert of 4.83 (very good) and the assessment of the media expert of 4.83 (very good). The assessment from expert practitioners got a score of 4.91 (very good), and students got a score of 4.93 (very good). It is concluded that PBL-based digital comic learning media is feasible to use in learning.